Regulations Concerning International Arbitral Awards in Indonesia: An Approach to the Theory of Legal Values by Gustav Radbruch - Supeno, Supeno; Yanti, Herma (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2022)
One of the aims that underlies the establishment of the board of arbitration is to keep business dispute settlement efficient. The principle of resolving disputes through arbitration is final and binding, indicating that this decision can be directly enforced. The law concerning Arbitration in Indonesia asserts that an arbitral award can be taken further for an appeal to a District Court, or it can even be revoked. This is normative research with a theoretical approach. The research results conclude that international arbitral awards in Indonesia do not correspond to Gustav Radbruch’s theory because it fails to guarantee proportional justice for all interests and fails to ensure legal certainty due to conflicts of norms that may harm one of the parties. The clauses in the law governing arbitration in Indonesia need revising to fit Gustav Radbruch’s theory by removing articles that are not accordance with the principle of justice, certainty and expediency, should be a guarantee that arbitration international awards will be recognized dan implemented in Indonesia without any interference from Indonesia courts. Keywords: reward, justice, legal certainty, utility